Pendampingan Literasi melalui Refleksi dan Evaluasi Pembelajaran dengan Menggunakan Pendekatan Deep Learning di SDN 2 Cimerang - Melanisa Steviani Gultom; Ayi Abdurahman (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This research aims to improve the literacy skills of elementary school students through learning assistance based on reflection and evaluation with a deep learning approach. The activities were conducted at SDN 2 Cimerang with the subjects being 5B grade students. The method used is Classroom Action Research (CAR) which consists of planning, implementation, observation, and reflection cycles. The initial observation results show that students tend to read mechanically and are unable to comprehend the meanings of the readings deeply. Through the application of a deep learning approach that integrates meaningful, mindful, and joyful learning, students begin to show improvements in critical thinking, reflective writing, and connecting texts with personal experiences. Teachers also started to implement formative evaluation and reflection as part of the learning strategy. The final results show that 80% of students experienced an improvement in literacy understanding. This approach has proven effective in creating an active, enjoyable, and meaningful learning environment, and is worth replicating in other elementary schools.